PENGARUH METODE PEMBELAJARAN DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR SEJARAH INDONESIA - Devi Junianti; Tundjung Tundjung (Herodotus: Jurnal Pendidikan IPS, 2019)
The purpose of this study was to determine: 1) The effect of learning methods on the learning outcomes of Indonesian history of high school students in Tangerang Regency. 2) The effect of student creativity on the results of Indonesian history learning by high school students in Tangerang Regency. 3) The interactive influence of student learning methods and creativity on the results of Indonesian history learning in high school students in Tangerang Regency. This study uses an experimental method. The results of the study: 1) There is a significant effect of learning methods on the learning outcomes of Indonesian History of high school students in Tangerang Regency. This is evidenced by the acquisition of sig 0.021 <0.05 and Fcount = 5.578. 2) There is a significant influence of students' creativity on the learning outcomes of Indonesian History of high school students in Tangerang Regency. This is evidenced by the acquisition of sig 0.029 <0.05 Fcount = 4.976. 3) There is a significant interactive effect of student learning methods and creativity on the learning outcomes of Indonesian History of high school students in Tangerang Regency. This is evidenced by the acquisition of sig0,000 <0.05 and Fcount = 56.925.